Deltamethrin resistance in Chagas disease vectors colonizing oil palm plantations: implications for vector control strategies in a public health-agriculture interface - Johan M. Calderón; Patricia Fuya; Liliana Santacoloma; Camila González (Parasites & Vectors, 2020)
Abstract Background Triatomine bugs are responsible for the vectorial transmission of the parasite Trypanosoma cruzi, etiological agent of Chagas disease, a zoonosis affecting 10 million people and with 25 million at risk of infection. Several triatomine species of the genus Rhodnius have been found inhabiting palm crowns where insects can find shelter in leaves axils and blood from palm-associated vertebrates. Rhodnius prolixus insects have been collected in oil palms in Colombia, and high T. cruzi infection rates were found. Since pest control is carried out in oil palm plantations, continuous exposure to insecticides could be occurring in these triatomines. Some insecticides suggested for pest control in oil palm plantations are also recommended for triatomine control in human dwellings. In this study, our objective was to assess if triatomines inhabiting oil palms exhibit resistance to deltamethrin, an insecticide used for vector control. Methods Rhodnius prolixus nymphs were sampled in oil palms located in Tauramena, Colombia. To determine deltamethrin resistance, biological and biochemical assays were carried out on fifth-instar nymphs from the F1 generation. For biological assays, pure and commercial deltamethrin were used, and in biochemical assays, activities of detoxifying enzymes related to pyrethroid resistance, such as oxidases, esterases and transferases, were quantified. Results Deltamethrin lethal dosage 50 and 90 in R. prolixus from oil palms was significantly higher than in those from a susceptible colony suggesting possible deltamethrin resistance. Moreover, mortality with commercial deltamethrin was very low in insects from oil palms. In biochemical assays, the activity of evaluated detoxifying enzymes was significantly higher in R. prolixus from oil palms than in those from the susceptible colony. Conclusions Possible deltamethrin resistance found in R. prolixus insects from oil palms could threaten traditional vector control strategies in urban settings if insecticide-resistant triatomines can migrate from oil palms plantations. In palm oil producer countries such as Colombia, the oil palm plantations are growing constantly during the last years. We suggest that pest control strategies in oil palm crops should include triatomine surveillance and toxicological monitoring, especially in zones with several Chagas disease cases.